Assessment of risk-stratified approach to thromboprophylaxis in hip arthroplasty patients: a prospective cohort study. Issue 1 (16th January 2023) - Bhaskarwar, Ajit P.; Kumar, Narinder
Abstract : Background: Venous thromboembolism (VTE) is a frequent and serious complication in orthopaedic surgeries of the lower limbs. Subsequent pulmonary embolism (PE) makes it the most common cause of death after joint replacement surgeries of the lower limbs. In this study, a multimodal approach for thromboprophylaxis was adopted in patients undergoing total hip replacement (THR) and hemiarthroplasty (HA), including pharmaceutical and mechanical agents recommended by the American Academy of Orthopaedic Surgeons (AAOS) as per risk stratified approach, and the effectiveness of the same was measured by clinical and radiographic assessment. Methods: This was a prospective observational longitudinal study with evaluation at multiple points of time carried out at a tertiary care orthopaedic center. The study included 66 consecutive patients who underwent hip replacement arthroplasty (45 THR, 21 HA). Mechanical and pharmacological (soluble aspirin) prophylaxis modalities for deep venous thrombosis (DVT) were administered to all patients after risk stratification. Patients were assessed for evidence of DVT at 2, 6, and 12 wk postoperatively by clinical tests and color Doppler flow imaging (CDFI). Results: This study confirmed efficacy of AAOS recommended risk stratified approach of thromboprophylaxis by combined use of soluble aspirin and various other mechanical measures in patients having standard risk for PE and bleeding undergoing THR or HA because none of the patients developed DVT per clinical assessment and confirmed by CDFI carried out at follow-up. Conclusions: Prevention of DVT as recommended by AAOS has proven to be effective as well as cheaper in moderate-risk patients undergoing hip replacement surgery. Though there were no major differences in complication rates in respect to other prophylaxis except prevalence of major bleeding was very low. Level of Evidence: Level II